Strategic asset or mandatory burden: The SME perspective on environmental sustainability actions - Aaltio, Emma (2025)
To develop effective policies and supporting methods to drive sustainable transition across industries, it is necessary to understand the environmental impact of companies in different sizes. However, in societal discussions regarding sustainability, small- and medium-sized enterprises (SMEs) are often overlooked despite their collective, significant environmental impact. Even sustainability initiatives, e.g., Corporate Sustainability Reporting Directive (CSRD), often target larger companies – with only an indirect influence on SMEs, which is not necessarily enough to engage SMEs in sustainability actions.